Validating an alternative method to predict thermoelectric generator performance. (15th May 2016) - Orr, B.; Taglieri, J.; Ding, L.C.; Akbarzadeh, A.
Graphical abstract: Highlights: Equations were derived that predict the power output and efficiency of TEGs. Experimental testing was conducted on 2 types of TEGs. The derived equations were found to be valid. It is not recommended to use the derived equations at high temperature differences. Abstract: When designing a system that utilises TEG (Thermoelectric generator) technology, it is required to know what will be the performance of the TEGs under the expected operating conditions. To do this, equations that model the performance of the TEG must be used. There are existing equations which predict the efficiency and power output of the TEGs but in this paper, alternative equations are derived which are far simpler than the existing equations to use. These derived equations predict the efficiency and maximum power output as a function of temperature difference. Parameters which describe the characteristics of the TEG such as the gradient of the current – voltage curve, gradient of the open circuit voltage – temperature difference curve and the thermal resistance are required to be able to use these equations. Testing was undertaken to find these parameters and to validate the output of these equations to the experimental results. It was found that the equations derived are valid but should not be used at very high temperature differences.